2002
DOI: 10.1007/s00203-002-0427-1
|View full text |Cite
|
Sign up to set email alerts
|

Aciduric Proteobacteria isolated from pH 2.9 soil

Abstract: Acidic (pH 2.9) soil was used as an inoculum to culture heterotrophic bacteria at pH values of 3-4. Four isolates were obtained; on the basis of 16S rDNA sequence, they were shown to be members of the beta- and gamma-Proteobacteria. The three isolates that were most closely related to Burkholderia spp. had simple nutritional requirements and could grow in glucose-mineral salts media; two of these used a broad array of organic substrates. The 16S rDNA sequence of the fourth isolate was most similar (96%) to Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…In an investigation of the bacterial structure of rice crops, we had previously found increased numbers of the phylum Proteobacteria in soil layers down to 300 cm in depth [20]. This result suggests that the members of the phylum Proteobacteria can survive in a variety of soil types, including those that present higher pH values [42], those that are acidic and those that have a low availability of nutrients [43]. The greatest decrease in abundance of Acidobacteria with increased depth is probably due to the aerophilic and acidophilic characteristics of the microorganisms that compose this phylum.…”
Section: Discussionmentioning
confidence: 99%
“…In an investigation of the bacterial structure of rice crops, we had previously found increased numbers of the phylum Proteobacteria in soil layers down to 300 cm in depth [20]. This result suggests that the members of the phylum Proteobacteria can survive in a variety of soil types, including those that present higher pH values [42], those that are acidic and those that have a low availability of nutrients [43]. The greatest decrease in abundance of Acidobacteria with increased depth is probably due to the aerophilic and acidophilic characteristics of the microorganisms that compose this phylum.…”
Section: Discussionmentioning
confidence: 99%
“…Enteric bacteria could encounter some of the bacteria containing genes that exhibit gene synteny with SPI-7 in the gut via contaminated food (food containing soil residue, for example). It is known, for example, that the soil bacterium B. fungorum is capable of surviving and growing in an acid environment (10) and thus may be able to survive in the acidic contents of the stomach. Whatever the source is, the potential transmissibility of these islands is emphasized by their insertions in tRNA sites such as tRNA pheU for SPI-7 and tRNA glyU for P. aeruginosa SG17M and in viaB for C. freundii.…”
Section: Discussionmentioning
confidence: 99%
“…Soil pH has frequently been shown to be the main predictor of overall soil bacterial community composition, diversity and the relative abundance of many individual taxa (Tiedje et al, 1999;Fierer and Jackson, 2006;Rousk et al, 2010;Griffiths et al, 2011). Although it is not known if Burkholderia distributions are related to soil pH, most studies that have reported their presence in soil were investigating acidic environments (Trân Van et al, 2000;Curtis et al, 2002;Salles et al, 2002;Belova et al, 2006;Garau et al, 2009;Aizawa et al, 2010). For instance, Burkholderia unamae could only be isolated from the rhizosphere of plants growing in soils, with a pH ranging from 4.5 to 7.1, but not from soils with a pH higher than 7.5 (Caballero-Mellado et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a survey of over 800 Australian soil samples revealed that B. pseudomallei was specifically associated with low pH soils, but not recovered from higher pH soils (Kaestli et al, 2009). Burkholderia species have also been isolated from acidic Sphagnum peat bogs (Belova et al, 2006;Opelt et al, 2007a;2007b), from root tissues of the highly acidifying cluster rooted Lupinus albus (Weisskopf et al, 2011) or from soils as acidic as pH 2.9 (Curtis et al, 2002). To the best of our knowledge, only one study reported isolation of Burkholderia strains from an alkaline environment (Estrada-de los .…”
Section: Introductionmentioning
confidence: 99%